Role of EGFR expressed on the granulosa cells in the pathogenesis of polycystic ovarian syndrome - Zhang, Jun-Hui; Zhan, Lei; Zhao, Ming-Ye; Wang, Jin-Juan; Xie, Fen-Fen; Xu, Zu-Ying; Xu, Qian; Cao, Yun-Xia; Liu, Qi-Wei (Frontiers in Endocrinology, 2022)
Polycystic ovarian syndrome (PCOS) is one of the most common endocrinological disorders affecting between 6 to 20% of reproductive aged women. However, the etiology of PCOS is still unclear. Epidermal growth factor receptor (EGFR) plays a critical role in the growth and development of ovarian follicles. In our previous study, we showed that the expression level of EGFR was significantly higher in the cumulus granulosa cells from women with PCOS than that of normal women, suggesting that EGFR may play a potential role in the pathogenesis of PCOS. The present study further evaluated the association between EGFR and PCOS through both in clinical observation and animal experiments. We firstly validated the differential expression of EGFR in cumulus granulosa cells between PCOS patients and normal subjects by qRT-PCR and immunofluorescence staining. Then we generated a mouse model (n=20) of PCOS by injecting dehydroepiandrosterone (DHEA). The PCOS mice were then injected with an E corpus GFR inhibitor (AG1478) (n=10), which significantly improved the sex hormone levels in the estrous cycle stage, and the serum levels of LH, FSH and testosterone were compared with the PCOS mice without EGFR inhibitor treatment (n=10). Decreasing the expression level of EGFR in the PCOS mice also improved the ovulatory function of their ovaries which was indicated by the multifarious follicle stage in these mice as compared with the PCOS mice without EGFR inhibitor treatment. Also, the number of corpopa lutea were higher in the control group and the EGFR inhibitor treated group than in the PCOS group. The sex hormone levels and reproductive function were not significantly different between the control mice and the PCOS mice treated with the EGFR inhibitor. Our results demonstrated that EGF/EGFR signaling affected the proliferation of cumulus granulosa cells, oocyte maturation and meiosis, and played a potential role in the pathogenesis of PCOS. Therefore, the selective inhibition of EGFR may serve as a novel strategy for the clinical management of PCOS.